Implementation of Legal Policy in Indonesia in Handling Illegal Immigrants - Tessar Bayu Setyaji; Zudan Arief Fakrulloh; Suparno Suparno (Jurnal Indonesia Sosial Sains, 2023)
Even though it is not a destination country, with the consequence of its geographical location, Indonesia is the final stopover for waves of asylum seekers and refugees going to the destination country, namely Australia. The presence of these illegal immigrants will raise demographic problems (population) and is related to social-economic conflicts and directly proportional to the crime rate. The fact that Indonesia is a country of transit for illegal immigrants is evident from the duration of their stay. As many as 17.50 percent of immigrant respondents stated that they lived in Indonesia for 2-4 weeks. It was that immigrants could pause for their next journey, change smuggling agents, or use transit as a separate strategy before entering Australian territory. Immigrants themselves when entering Indonesian territory must have valid documents by the laws and regulations in force in Indonesia as referred to in Article 8 paragraph (1) of Law Number 6 of 2011 concerning Immigration. Law enforcement against foreign nationals is aimed at issues of falsification of identity, lack of documents, registration of foreigners and provision of foreign control books, abuse of residence permits, illegal entry or stay illegal, expiry of stay permit, being in Indonesia outside monitoring by raids and geographic vulnerability in crossings.